Synthesis, Biological and Pharmacological Activities of Some New Derivatives of 5-Aryl-1,3,4-oxadiazolin-2-thiones - Aruna Devi, M.; Reddy, V.M. (Asian Journal of Chemistry, 2010)
Four different S-(5-aryl-1,3,4-oxadiazol-2-yl)mercaptoacetic acids were prepared from the respective 5-aryl-1,3,4-oxadiazol-2-thiones on reaction with chloroacetic acid. Each of these acids has been converted into its acid chloride using thionyl chloride and condensed with three different secondary amines: dicyclohexylamine, morpholine and piperidine. The products obtained in each case were purified and characterized as the respective N,N-disubstituted S-(5- aryl-1,3,4-oxadiazol-2-yl) mercaptoacetamides. Alternatively, acid chlorides were also reacted in situ with two different N-substituted 2-aminoethanols and the products were characterized as the respective 2-N,N-substituted aminoethyl S-(5-aryl-1,3,4-oxadiazol-2-yl) mercaptoacetates. Similarly the acid chlorides in situ were also substituted to a reaction with 2-methoxyethanol and 2-ethoxyethanol, the products were purified and characterized as the respective esters, i.e., 2-alkoxyethyl S-(5-aryl-1,3,4-oxadiazol-2-yl) mercaptoacetates. On the basis of their analytical and spectral data, the new derivatives of oxadiazol-2-thiones were evaluated for their antimicrobial (antibacterial and anti fungal) activities, by standard methods and found to exhibit relatively good antibacterial activity specifically against P. auroginosa and antifungal activity against C. lunata. The fenamates in which the carboxylic group replaced by oxadiazolin-2-thione were reported to exhibit antiinflammatory activity by inhibiting the cyclooxygenase and 5-lipoxygenase activities. Ibuprofen, a known NSAID was structurally modified by a similar replacement of its carboxylic group with oxadizolin-2-thione and was to be effective at an oral dose of 100 ug/kg (bw). Some oxadiazolyl trizoles were reported to exhibit invitro antimicrobial properties. A series of quinazolinonyloxadiazoles were synthesized and found to show good oral hypoglycemic activity. Some of the N-mannich bases of β-(N-substituted indolyl)-1,3,4-oxadiozolin-2- thiones were synthesized and found to exhibit antiinflamatory activity. A similar compound with an acetic acid hydrazino group at 3-position were found to show a broad spectrum antibacterial activity. Herein, the synthesis, characterization, biological and pharmacological activities of some S-substituted analogues of 5-substituted 1,3,4-oxadiazolin-2-thiones are reported.